Ramadan during pregnancy and offspring health outcomes over the life course: a systematic review and meta-analysis - Pradella, Fabienne; Witte, Paul; Ewijk, Reyn van (Human reproduction update, 2024)
Intermittent fasting, such as during Ramadan, is prevalent among pregnant women. However, the association between Ramadan during pregnancy and offspring health along the life course has not been fully established.Fetal programming research indicates that prenatal exposures, particularly during early pregnancy, can cause long-term structural and physiological changes that adversely affect offspring health. Our objective was to systematically identify and assess the evidence regarding Ramadan during pregnancy.A total of 31 studies were sourced from PubMed, EMBASE, Web of Science, and EconLit. Included studies evaluated outcomes in individuals with prenatal Ramadan exposure, compared to unexposed Muslim controls. Main outcomes were birth weight, gestational length, and sex ratio in newborns; height, mortality, and cognition in children; and disabilities, chronic diseases, and human capital accumulation in adults. Each study was evaluated for risk of bias. The overall quality of evidence was appraised using the GRADE system. Random-effects meta-analyses were conducted for outcomes analyzed in at least three primary studies.The initial search identified 2933 articles, 1208 duplicates were deleted. There were 31 publications fulfilled the eligibility criteria for the qualitative synthesis; 22 studies were included in meta-analyses. The overall quality of the evidence was low to moderate and differed by study design and outcome. Among newborns, prenatal Ramadan exposure was not associated with birth weight (mean difference (MD) −3 g (95% CI −18 to 11; I2 = 70%) or the likelihood of prematurity (percentage point difference (PPD) 0.19 (95% CI −0.11 to 0.49; I2 = 0%)). The probability that the newborn is male was reduced (PPD −0.14 (95% CI −0.28 to −0.00; I2 = 0%)). This potentially reflects sex-specific mortality rates resulting from adverse in utero circumstances. In childhood, the exposed performed slightly poorer on cognitive tests (MD −3.10% of a standard deviation (95% CI −4.61 to −1.58; I2 = 51%)). Height among the exposed was reduced, and this pattern was already visible at ages below 5 years (height-for-age z-score MD −0.03 (95% CI −0.06 to −0.00; I2 = 76%)). A qualitative literature synthesis revealed that childhood mortality rates were increased in low-income contexts. In adulthood, the prenatally exposed had an increased likelihood of hearing disabilities (odds ratio 1.26 (95% CI 1.09 to 1.45; I2 = 32%)), while sight was not affected. Other impaired outcomes included chronic diseases or their symptoms, and indicators of human capital accumulation such as home ownership (qualitative literature synthesis). The first trimester emerged as a sensitive period for long-term impacts.Despite the need for more high-quality studies to improve the certainty of the evidence, the synthesis of existing research demonstrates that Ramadan during pregnancy is associated with adverse offspring health effects in childhood and especially adulthood, despite an absence of observable effects at birth. Not all health effects may apply to all Muslim communities, which are diverse in backgrounds and behaviors. Notably, moderating factors like daytime activity levels and dietary habits outside fasting hours have hardly been considered. It is imperative for future research to address these aspects.PROSPERO (CRD42022325770).